Incorporation of a high-level soccer player into the team after a muscle injury: A case study (Incorporación de un jugador de fútbol de alto nivel en el equipo después de una lesión muscular: Un estudio de caso) - Andrés Vargas Fuentes; Iban Urkiza Ibaibarriaga; Susana María Gil Orozko (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The aim of the study was to observe the evolution of the external load of a soccer player who just joined the team after a recovered injury.13 male football players of a soccer team (20.9 ± 1.7 years, 1.80 ± 0.05 m, 73.1 ± 5.3 kg) belonging to the 2nd division B participated in this study. After 30 days off following a hamstring injury a player started to train with the team. The next week his injury relapsed, so he had to stop training for another week. Finally he was re-incorporated to the team. External load was measured in the injured player (P) and the rest of the players of the team (T) using GPS devices (GPSport) during week 1 and week 2. The variables measured were: distance at high intensity (DHI; >14 km/h) and distance at sprint (S; >24 km/h). Besides, the number of times they entered the different acceleration rates: (Acc) 1 (0-2 m/s/s), Acc2 (2-3 m/s/s) and Acc3 (3-5 m/s/s) and the number of times they entered the different deceleration rates: (Dec) 1 (0-2 m/s/s), Dec2 (2-3 m/s/s) and Dec3 (3-5 m/s/s). During the first week of training, P performed longer DHI and S than T. Moreover, P performed higher acc1, acc2, acc3, dec1, dec2 and dec3 than T. In contrast, during the second week, T performed longer DHI and S than P. However, P performed higher acc1, acc2, acc3, and dec1 than T. However, similar values were found in dec2 and dec3 in P and T. It was observed that the acc and dec in both weeks indicated a higher peripheral muscle work in P. Therefore, according to the nature of the injury a modification or even avoidance of certain exercises should be considered especially those exercises that directly impact on the repaired muscles. Key words: Hamstring, injury, incorporation and football.